(2S)-2-[(Phenylsulfinyl)methyl]pyrrolidine-Catalyzed Efficient Stereoselective Michael Addition of Cyclohexanone and Cyclopentanone to Nitroolefins - Singh, Kamal Nain; Singh, Paramjit; Kaur, Amarjit; Singh, Pushpinder; Sharma, Sandeep Kumar; Khullar, Sadhika; Mandal, Sanjay K. (Synthesis, 2013)
(2S)-2-[(Phenylsulfinyl)methyl]pyrrolidine, derived from l-proline, has been demonstrated as an efficient organocatalyst for the asymmetric Michael addition of cyclohexanone and cyclopentanone to β-nitrostyrenes. This pyrrolidine-based catalyst bearing a sulfoxide moiety was used to synthesize various γ-nitro carbonyl compounds in high yield (up to 97%) with excellent stereoselectivity (up to >99:1 dr and >99% ee) without the use of any additive.
Keywords: Michael addition reaction; organocatalyst; amino sulfoxide; nitroolefins; ketones